India Stack—Digital Infrastructure as Public Good. - RAGHAVAN, VIVEK; JAIN, SANJAY; VARMA, PRAMOD (Communications of the ACM, 2019)
The article discusses the India Stack project of digitizing India, which consists of numerous application programming interfaces (APIs), with a particular focus on the Indian government's Aadhaar program to develop identification (ID) cards for Indians. An overview of the Aadhaar program's use of biometric authentication to ID people, including privacy concerns with this, is provided. The development of the Unified Payments Interface (UPI) for electronic payment is discussed.